Implementation of the Basel Core Principles for Effective Banking Supervision, Experiences, Influences, and Perspectives. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
NULL.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet